Antioxidants activity of various extracts of curcuma longa linn (pucuk kunyit), Syzygium polyanthum (daun samak) and Diplazium Esculentum (pucuk paku) - Khor, Yee Heng (2015)
Antioxidant compounds in food play an important role as health protecting body system. Plant sourced food antioxidants like vitamin C, vitamin E, carotenes, phenolic acid, phytate and phytoestrogens have been recognized as having the potential to reduced disease risk. The aim of this study was to screen various solvent extracts of three selected Malaysian plant Curcuma longa Linn, Syzygium polyanthum and Diplazium esculentum to display the potential of antioxidant activity in order to find possible sources for future novel antioxidants in food and pharmaceutical formulations. Detail study was performed by using six different types of solvent which are petroleum ether, chloroform, ethyl acetate, acetone, ethanol and distilled water to determine the antioxidant activity of three selected plants. Microwave assisted extraction technique are also used in order to get the maximum antioxidant potential. DPPH radical scavenging assay are used to estimate the antioxidant activity on each plant extract and ascorbic acid was used as standard at different concentration. The results showed that, there was significant different (P < 0.05) in antioxidant activity for C. longa L., S. polyanthum and D. esculentum in different type of solvent. The highest DPPH inhibition activity was observed with ethanolic extract of C. longa L. (86.77 ± 0.95 %), S. polyanthum (88.76 ± 1.15 %) and D. esculentum (84.84 ± 1.39 %). Overall the highest inhibition showed by ethanol extracts of S. polyanthum which comparable to ascorbic acid at 10.92 μg/ml. These findings suggest that, further works are required to identify individual phenolic compounds which might contribute to the antioxidant activities in the plant samples.